A Himalayan prince between India and Europe: Suchet Singh of Chamba and the limits of colonial subjectivity. (April 2023) - Moran, Arik; Hasson, Michal
This article discusses the life-story of Suchet Singh (1841–1896). The ruler of the Himalayan kingdom of Chamba, Singh was deposed by the colonial authorities soon after his accession in 1870, and spent the rest of his life seeking restitution. We argue that the strategies employed by Singh, who combined appeals to the international press with political manoeuvrings in India and Europe, evince a novel type of cosmopolitanism. This new development allowed elites from the colonies to contest the empire by exploiting unprecedented technological advancements in communications and travel alongside the support of a widening liberal lobby in the metropole. While Singh ultimately failed to regain his patrimony and died destitute in exile, his life story demonstrates the capacity of judicious engagement with the public sphere and the cultivation of global support-networks to improve the standing of colonial subjects in the Age of Empire.